The mTOR Inhibitor Rapamycin Prevents General Anesthesia-Induced Changes in Synaptic Transmission and Mitochondrial Respiration in Late Postnatal Mice - Ju, Xianshu; Ryu, Min Jeong; Cui, Jianchen; Lee, Yulim; Park, Sangil; Hong, Boohwi; Yoo, Sungho; Lee, Won Hyung; Shin, Yong Sup; Yoon, Seok-Hwa; Kweon, Gi Ryang; Kim, Yoon Hee; et al. (Frontiers in Cellular Neuroscience, 2020)
Preclinical animal studies have continuously reported the possibility of long-lasting neurotoxic effects after general anesthesia in young animals. Such studies also show that the neurological changes induced by anesthesia in young animals differ by their neurodevelopmental stage. Exposure to anesthetic agents increase dendritic spines and induce sex-dependent changes of excitatory/inhibitory synaptic transmission in late postnatal mice, a critical synaptogenic period. However, the mechanisms underlying these changes remain unclear. Abnormal activation of the mammalian target of rapamycin (mTOR) signaling pathway, an important regulator of neurodevelopment, has also been shown to induce similar changes during neurodevelopment. Interestingly, previous studies show that exposure to general anesthetics during neurodevelopment can activate the mammalian target of rapamycin (mTOR) signaling pathway. This study therefore evaluated the role of mTOR signaling after exposing postnatal day (PND) 16/17 mice to sevoflurane, a widely used inhalation agent in pediatric patients. We first confirmed that a 2 hours exposure of 2.5% sevoflurane could induce widespread mTOR phosphorylation in both male and female mice. Pretreatment with the mTOR inhibitor rapamycin not only prevented anesthesia-induced mTOR phosphorylation, but also the increase in mitochondrial respiration and male-dependent enhancement of excitatory synaptic transmission. However, the changes in inhibitory synaptic transmission that appear after anesthesia in female mice were not affected by rapamycin pretreatment. Our results suggest that mTOR inhibitors may act as potential therapeutic agent for anesthesia-induced changes in the developing brain.